Between Decentralized Planning and Neo-liberalism: Challenges for the Survival of the Indigenous People of Kerala, India - Darley Jose Kjosavik and Nadarajah Shanmugaratnam (S P & A, 2006)
This paper examines the experiences of decentralization under successive political regimes in Kerala in the context of neo-liberal policies, with reference to the impact on the lives of adivasi (indigenous) communities. The Communist Party-led government had been implementing a home-grown programme of decentralized planning since  until it lost power to the Congress Party-led conservative coalition in  . In the context of the accelerated structural adjustment and liberalization of the national government, the new government amended its predecessor’s programme with a reduced role for the state bureaucratic and political actors in mobilizing people for planning and implementing projects at the local level. Based on a comparative analysis, the authors argue that the new programme has so far not been successful as regards enabling marginalized groups such as the indigenous communities to resist exclusion and move out of their states of deprivation. The study also shows that the withdrawal of the state from the social and economic sectors has adversely affected these groups.